THE INFLUENCE OF PRICE AND PRODUCT VARIETY ON PURCHASING DECISIONS FOR MOUNTEA - Ardiprawiro (Asosiasi Dosen Muda Indonesia, 2023)
The aim of this study was to examine how Mountea's purchase decisions were affected by product prices and product variants. Quantitative primary data were employed in the analysis in this study, and the following tests were run: validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, T test, F test, and coefficient of determination. The study's valid data were gathered by 100 participants in the form of a Google Form, which was utilized to administer the questionnaire. Non-probability sampling using the purposive sample technique was the sampling strategy used in this investigation. SPSS version 26 was used as the testing software. The findings indicated that Mountea's purchase decisions were partially influenced by the results of the variable pricing and product variety. Purchase decisions on Mountea are influenced simultaneously by product variety and price changes.